Improving Understanding of Legal Regulations on the Use of Motor Vehicle Exhaust Pipes Among Students at SMAN 40 Jakarta (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
High school students, as Indonesian citizens, have a responsibility to maintain a healthy and comfortable environment, including reducing noise levels. The main problems faced by partners, in this case SMAN 40 Jakarta, are (1) limited access to legal information and (2) a lack of understanding of the legal provisions relating to the use of motor vehicle exhausts. This legal education activity aims to increase students' knowledge and awareness of the importance of complying with legal regulations related to the use of motor vehicle exhausts. This outreach activity was carried out using a participatory action research approach combined with lectures and interactive discussions. Implementing the programme significantly improved students' understanding of, and awareness of the importance of compliance with, these legal regulations. Before the counselling session, only 16% of students understood the regulations; this figure increased to 98% afterwards.  Alongside this increase in understanding, there was also greater compliance with the rules regarding motor vehicle exhausts. This resulted in fewer violations and helped create a healthier environment.